Refractory Epilepsy-MRI, EEG and CT scan, a Correlative Clinical Study - Nikodijevic, Dijana; Baneva-Dolnenec, Natalija; Petrovska-Cvetkovska, Dragana; Caparoska, Daniela (ID Design 2012/DOOEL Skopje, 2016)
Refractory epilepsies (RE), as well as, the surgically correctable syndromes, are of great interest, since they affect the very young population of children and adolescents. The early diagnosis and treatment are very important in preventing the psychosocial disability. Therefore MRI and EEG are highly sensitive methods in the diagnosis and localization of epileptogenic focus, but also in pre-surgical evaluation of these patients. The aim of our study is to correlate the imaging findings of EEG, MRI and CT scan in refractory symptomatic epilepsies, and to determine their specificity in detecting the epileptogenic focus.